Enhancing the visitor experience with immersive technologies and gaming: The Monserrate use case - Portugal, C.; Vaz, D.; Dias, M. S.; Trocado, P.; Prata, A.; Brito e Abreu, F. (Smart life and smart life engineering: Current state and future vision, 2025)
Immersive technologies, such as augmented reality (AR) and virtual reality (VR), are effective technologies being implemented across diverse fields. We propose an AR/VR-based web app to be applied in the cultural tourism field with the objective of enhancing the visitors’ experience of the Monserrate Palace, part of a UNESCO cultural landscape located in Sintra, Portugal, managed by Parques de Sintra ś Monte da Lua SA. This chapter overviews the state of the art on immersive technologies in cultural heritage sites and the visitor experience at these sites. Then, it exposes the palace’s historical and cultural significance and some of the challenges it faces in engaging its visitors. The potential applications of immersive technologies in the palace are explored, including interactive storytelling and immersive experiences that allow for a higher level of visitor engagement. Next, it addresses potential challenges and limitations of deploying the proposed solution in the palace, such as technical constraints and preservation concerns. It then concludes with a reŕection on the significant potential of AR and VR in enriching the immersive experience of Monserrate Palace, offering new possibilities for engaging with cultural heritages and creating a memorable and enjoyable visit for modern audiences.